2011
DOI: 10.5194/acp-11-1697-2011
|View full text |Cite
|
Sign up to set email alerts
|

North American isoprene influence on intercontinental ozone pollution

Abstract: Abstract. Changing land-use and climate may alter emissions of biogenic isoprene, a key ozone (O 3 ) precursor. Isoprene is also a precursor to peroxy acetyl nitrate (PAN) and thus affects partitioning among oxidized nitrogen (NO y ) species, shifting the balance towards PAN, which more efficiently contributes to long-range transport relative to nitric acid (HNO 3 ) which rapidly deposits. With a suite of sensitivity simulations in the MOZART-2 global tropospheric chemistry model, we gauge the relative importa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 72 publications
2
61
0
Order By: Relevance
“…Fiore et al (2010) showed that interannual variability in isoprene emissions, which can be as large as 20-30 % in summer months Müller et al, 2008), can influence seasonally averaged PAN mixing ratios downwind. However this impact is most pronounced in summer months when isoprene emissions are largest, and it is not likely to have driven the differences we observed during spring (Fiore et al, 2011(Fiore et al, , 2010.…”
Section: Other Potential Natural Drivers Of Pan Variabilitymentioning
confidence: 86%
“…Fiore et al (2010) showed that interannual variability in isoprene emissions, which can be as large as 20-30 % in summer months Müller et al, 2008), can influence seasonally averaged PAN mixing ratios downwind. However this impact is most pronounced in summer months when isoprene emissions are largest, and it is not likely to have driven the differences we observed during spring (Fiore et al, 2011(Fiore et al, , 2010.…”
Section: Other Potential Natural Drivers Of Pan Variabilitymentioning
confidence: 86%
“…The impact of North American (NA) isoprene on European ozone has been assessed, and it has been shown that future increases in NA isoprene emissions could offset decreases in EU surface O 3 resulting from controls on NA anthropogenic emissions (Fiore et al, 2011). Archibald et al (2011) showed that there is a significant impact of mechanism uncertainties on the global impact of isoprene chemistry on ozone.…”
Section: Role Of Biogenics In the Formation Of Ozonementioning
confidence: 99%
“…Simpson, 1995;Roberts et al, 2006; or the composition of the global troposphere (e.g. von Kuhlmann et al, 2004;Folberth et al, 2006;Fiore et al, 2011). By exploiting the sensitivity studies described in Sect.…”
Section: The Influence Of Bvoc Emissions On Global Tropospheric Compomentioning
confidence: 99%